Library and Information Services in Central Library of Aligarh Muslim University From the Teachers’ Point of View: A Survey - Naushad Ali, P. M.; Ehsan Hasan, M. D. (Journal of Information and Knowledge, 2006)
Aligarh Muslim University has a long history of academic excellence. It has produced many eminent personalities in different fields. The Central Library of the University has given the needed Phillip to the excellent record of the University. An assessment of the library resources and services by the researchers has been made and presented in this article.